Treatment of retinal pigment epithelial detachment with antiangiogenic therapy - Luis Arias (Dove Medical Press, 2010)
Luis AriasDepartment of Ophthalmology, Bellvitge University Hospital, Barcelona, SpainPurpose: Evaluate the efficacy of pegaptanib, a selective anti-vascular endothelial growth factor (VEGF) agent, and bevacizumab, a nonselective anti-VEGF agent, for retinal pigment epithelial detachment (PED) associated with occult choroidal neovascularization (CNV) secondary to age-related macular degeneration (AMD).Methods: Prospective, comparative, nonrandomized pilot study included patients with PED comprising >50% of total lesion in subfoveal location with visual acuity (VA) 20/40–20/400 and lesions either previously untreated or treated only with photodynamic therapy/verteporfin. Seven patients received pegaptanib 0.3 mg intravitreally (IVT); eight received IVT bevacizumab 1.25 mg. Follow-up occurred every 4–6 weeks for 6 months. Reinjection of initial medication occurred if there was intra- or subretinal fluid observed by optical coherence tomography (OCT) or increased PED. Endpoints were mean changes from baseline to month 6 in VA (ETDRS) and foveal thickness.Results: At baseline, mean VA was lower, and mean foveal thickness was greater in pegaptanib versus bevacizumab-treated patients (36.1 vs 49.5 letters; 470.4 vs 321.1 μm). Mean improvements to month 6 in VA and foveal thickness were greater for pegaptanib (VA: +9.1 vs +7.2 letters; foveal thickness: −88.2 vs −52.9 μm). On average, pegaptanib-treated patients had slower but more sustained improvement in VA and foveal thickness; bevacizumab-treated patients showed rapid improvement with a slow return towards baseline. Both agents were well tolerated. Conclusion: Intravitreal injections of pegaptanib or bevacizumab are both efficacious and safe treatments for PED associated with occult CNV secondary to AMD.Keywords: bevacizumab, pegaptanib, retinal pigment epithelial detachment